Realizing Interfacial Electron/Hole Redistribution and Superhydrophilic Surface through Building Heterostructural 2 nm Co0.85Se‐NiSe Nanograins for Efficient Overall Water Splittings. Issue 7 (19th May 2022) - Ye, Fei; Zhang, Lin; Lu, Chengjie; Bao, Zhuoheng; Wu, Zeyi; Liu, Qiang; Shao, Zongping; Hu, Linfeng
Abstract: Electrochemical overall water splitting using renewable energy input is highly desirable for large‐scale green hydrogen generation, but it is still challenged due to the lack of low‐cost, durable, and highly efficient electrocatalysts. Herein, 1D nanowires composed of numerous 2 nm Co0.85 Se‐NiSe nanograin heterojunctions as efficient precious metal‐free bifunctional electrocatalyst are reported for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in alkaline solution with the merits of high activity, durability, and low cost. The abundant microinterface among the ultrafine nanograins and the presence of lattice distortion around nanograin interface is found to create a superhydrophilic surface of the electrocatalyst, which significantly facilitate the fast diffusion of electrolytes and the release of the formed H2 and O2 from the catalyst surface. Furthermore, synergic effect between Co0.85 Se and NiSe grain on adjusting the electronic structure is revealed, which enhances electron mobility for fast electron transport during the HER/OER process. Owing to these merits, the rationally designed Co0.85 Se‐NiSe heterostructures display efficient overall water splitting behavior with a low voltage of 1.54 V at 10 mA cm −2 and remarkable long‐term durability for the investigated period of 50 h. Abstract : Superhydrophilic surface and interface electron structure tuning can be simultaneously realized in ultrafine, 2 nm Co0.85 Se, NiSe nanograin‐based Co0.85 Se‐NiSe nanowire arrays, which delivers superior overall water splitting performance with a low voltage of 1.54 V at 10 mA cm −2 and long‐term durability for the investigated period of 50 h.